Artesunate Inhibits the Development of Esophageal Cancer by Targeting HK1 to Reduce Glycolysis Levels in Areas With Zinc Deficiency - Jin, Jing; Guo, Dongli; Wang, Yingying; Jiao, Wenpeng; Li, Daojuan; He, Yutong (Frontiers in Oncology, 2022)
Esophageal cancer (EC) threatens many lives in China, especially in areas with high incidences of EC. Our previous studies proved that zinc deficiency (ZD) promotes the cell cycle, thus promoting the progression of EC in areas with a high incidence of EC. Artesunate could inhibit the cell cycle, thereby inhibiting the progression of EC. In this study, we first demonstrated the mechanism by which artesunate inhibits EC in vitro and then demonstrated that artesunate could reverse the ZD-promoted progression of EC before EC occurred in vivo. The results showed that artesunate could inhibit the cell cycle, metastasis and glycolysis of EC cells. Artesunate could target HK1, promote HK1 degradation, and reduce the levels of HIF-1α and PKM2 expression, which are key glycolysis enzymes. The in vivo results showed that ZD could increase the expression of HK1 and increase the incidence of EC. Artesunate reduced the incidence of EC and decreased the level of HK1 expression before EC occurred. Artesunate has an anti-EC effect by inhibiting aerobic glycolysis and has the potential to be a drug that prevents EC in areas with a high risk of EC.